2007
DOI: 10.1111/j.1460-9568.2007.05641.x
|View full text |Cite
|
Sign up to set email alerts
|

Environment enrichment rescues the neurodegenerative phenotypes in presenilins‐deficient mice

Abstract: Presenilin (PS) 1 and 2 conditional double knockout (cDKO) mice show progressive memory dysfunction and forebrain degeneration. Gene expression profiling results revealed a strong activation of immunity and inflammation responses in the brains of 10-month-old cDKO mice. As environmental enrichment (EE) has been shown to be able to improve memory and induce neurogenesis of the brain, we assessed the effects of EE on the memory performance and the neurodegeneration in cDKO mice. We found that EE effectively enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 42 publications
5
34
1
Order By: Relevance
“…These tests evaluated the bar pressure response as a learning determinant and found a significant improvement in the performance of animals kept in enriched environments. These results corroborate other studies that showed the influence of EE on cognition in rats 17,18 , mice 21,22 , rabbits 23 and pig…”
Section: Discussionsupporting
confidence: 92%
“…These tests evaluated the bar pressure response as a learning determinant and found a significant improvement in the performance of animals kept in enriched environments. These results corroborate other studies that showed the influence of EE on cognition in rats 17,18 , mice 21,22 , rabbits 23 and pig…”
Section: Discussionsupporting
confidence: 92%
“…Microarray analysis was performed and analyzed as previously described (Dong et al, 2007;Li et al, 2011). Briefly, the cortex tissues from each group were pooled (5 mice/pool), and total RNA was isolated using the Agilent Total RNA Isolation Mini Kit (Agilent, USA) for cDNA synthesis.…”
Section: Dna Microarray Experimentsmentioning
confidence: 99%
“…There is consolidated evidence to show that the characteristics of the housing environment have a marked influence on the behaviour and welfare of animals, both those raised for biomedical investigation or farm animals (Beattie et al, 2000;Olsen et al, 2002;Laviola et al, 2004;Dong et al, 2007;Brenes et al, 2008). In particular, the provision of straw seems to represent a suitable strategy to alleviate the presence of injurious behaviours in swine (Petersen et al, 1995;Kelly et al, 2000;Guy et al, 2002;Van de Weerd et al, 2006;Studnitz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%